Matrices of Fibonacci Numbers - Kumar, Nand Kishor; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2025)
This paper describes the matrix representation of Fibonacci numbers. The interaction between number theory and linear algebra is emphasized by the study of Fibonacci numbers using matrices. This viewpoint not only makes calculation easier, but it also reveals the sequence's underlying structural characteristics.